Ytterbium ion promotes apoptosis of primary mouse bone marrow stromal cells - 戴春燕 陈士柱 王朝 张良 葛昆 张金超 (Journal of rare earths, 2015)
One of the main target organs for the lanthanides （Ln） is bone. Previous studies revealed that ytterbium （Yb） produced damage to the skeletal system in vivo. But the effects of Yb3＋ on bone marrow stromal cells （BMSCs） in vitro had not been reported. In this paper, cell viability, apoptosis, mitochondrial membrane potential （MMP）, reactive oxygen species （ROS） and lactate dehy- drogenase （LDH） were measured in order to study the effects of Yb3＋ on BMSCs. The results indicated that Yb3＋ displayed a slight positive effect on the BMSCs viability at concentrations of 1 x 104, 1 × 105, and 1 x 104 mol/L, but turned to decrease the viability of BMSCs at the highest concentration of 1 × 103 mol/L for 24, 48 and 72 h. Yb3＋ at 1 x 103 mol/L promoted apoptosis of BMSCs, in- creased the levels of ROS and LDH, and decreased MMP in BMSCs. It suggested that the precipitate of YbPO4 might decrease the viability of BMSCs. Yb3＋ induced the apoptosis of BMSCs via mitochondrial pathway. The results might be useful for more rational application of Yb-based compounds in the future.